'Should I post this one?': An ethnography on social media's effect on the tourist gaze - Viðja Jónasdóttir 1994- (2019)
The goal of this paper is to elucidate and define the possible effects that increased social media usage by travelers have had on the tourist gaze, as well as their performance and their selves. Tourist destinations in and around Reykjavík will be used as research sites for observation: the cathedral Hallgrímskirkja, the sculpture Sun Voyager and the Blue Lagoon. Photos which tag these locations on Instagram, a visually orientated social media platform, were analyzed, where observations gathered from these photos were kept in mind and compared to the actual performance of tourists at the same locations. During analysis, a conclusion was reached that social-media use has indeed effected the tourist gaze and performance, both based on the observations made during the research and on previously existing theories having to do with the tourist gaze, the self, consumption, and performance. As they seem to focus both their gaze and performance with the goal in mind of taking the perfect photo to share with others. Markmið rannsóknarinnar er að kanna og skilgreina möguleg áhrif sem aukin samfélagsmiðlanotkun hefur haft á áhorf ferðamanna á ferðamannastöðum, þá sérstaklega í tengslum við iðkun, neyslu og sjálfið. Horft verður sérstaklega til Hallgrímskirkju, Sólfarsins og Bláa Lónsins og hvernig áhorf og iðkun ferðamanna í tengslum við ljósmyndun mótast út frá samfélagsmiðlum, einkum Instagram, vegna áherslu þess á myndrænt efni. Etnógrafía var gerð þar sem áhersla var lögð á sjónrænar aðferðir í þátttakanda athugun á athöfnum ferðamannana á völdum áfangastöðunum. Kerfisbundin greining var gerð á myndum sem deilt var á Instagram sem og tengdar (taggaðar) við staðina annars vegar og hins vegar á þeim könnunum sem gerðar voru á vettvangi. Ályktað var að samfélagsmiðlar og aukin tækni hefur haft áhrif á iðkun og áhorf ferðamenn, sérstaklega með það í huga að ná mynd sem þau telja að þau geti deilt með öðrum.